Exploring the interstellar medium of NGC 891 at millimeter wavelengths using the NIKA2 camera - Katsioli S.; Adam R.; Ade P.; Ajeddig H.; André P.; Artis E.; Aussel H.; Baes M.; Beelen A.; Benoît A.; Berta S.; Bing L.; et al. (EPJ Web of Conferences, 2024)
In the framework of the IMEGIN Large Program, we used the NIKA2 camera on the IRAM 30-m telescope to observe the edge-on galaxy NGC 891 at 1.15 mm and 2 mm and at a FWHM of 11.1” and 17.6”, respectively. Multiwavelength data enriched with the new NIKA2 observations fitted by the HerBIE SED code (coupled with the THEMIS dust model) were used to constrain the physical properties of the ISM. Emission originating from the diffuse dust disk is detected at all wavelengths from mid-IR to mm. while mid-lR observations reveal warm dust emission from compact H II regions. Indications of mm excess emission have also been found in the outer parts of the galactic disk. Furthermore, our SED fitting analysis constrained the mass fraction of the small (< 15 Å) dust grains. We found that small grains constitute 9.5% of the total dust mass in the galactic plane, but this fraction increases up to ~ 20% at large distances (|z| > 3 kpc) from the galactic plane.